THE EFFECT OF THIN CAPITALIZATION AND PROFITABILITY ON TAX AVOIDANCE IN MANUFACTURING COMPANIES FOUND ON THE MALAYSIA STOCK EXCHANGE - Rika Nandini (Journal of Taxation Analysis and Review, 2023)
The purpose of this study was to determine the effect of Thin Capitalization and Profitability on Tax Avoidance. The object of research used in this study is a food and beverage manufacturing company listed on the Bursa Malaysia from 2019 to 2021. The number of samples used in the study were 40 data samples. This research uses Descriptive Statistical Test, Classical Assumption Test and Model Feasibility Test. The results of this study indicate that thin capitalization has a positive effect on tax avoidance in manufacturing companies listed on the malaysia stock exchange. Profitability has a negative effect on tax avoidance in manufacturing companies listed on the Malaysian stock exchange.